(Study of the Prophetic Hadiths in the Book of Ibn jiniy (Alkhasayis - Okasha, Tamador Ibrahim Abd El-kader (Journal of Islamic Sciences, 2019)
The importance of the research from being a topic related to the science of Hadith, where he studies the conversations cited by Ibn jiniy in his book (Alkhasayis). This research came in the introduction and two Chapters, the first of which dealt with the definition of Ibn jiniy and his book (Alkhasayis), and the other dealing with the conversations contained in the book of (Alkhasayis) of Ibn jiniy by study and then explain the strange words, and one of the most important results of the research that Ibn jiniy quotes the correct, (Hasnah), weak, false Hadiths.